OFDM synchronization system using wavelet transform for symbol rate detection - Masaru Sawada; Quang Ngoc Nguyen; Mohammed Mustafa Alhasani; Cutifa Safitri; Takuro Sato (Universitas Ahmad Dahlan, 2020)
In radio communications, using wavelet signal analysis to recover the symbol rate timing clock of orthogonal frequency-division multiplexing (OFDM) is a new approach that can tolerate signal distortion from intersymbol interference (ISI) and intercarrier interference of encoding digital data on multiple carrier frequencies. Typically, the reception synchronization with wavelet signal analysis in OFDM can improve the performance over the fourier transform-based OFDM. However, a synchronization procedure that is stable against distortion and noise is essential to diminish the symbol synchronization establishment and operation sampling period. In this paper, we propose an OFDM synchronization system and analyze the impact of the wavelet denoise procedure on the OFDM system, which extracts the symbol rate of the OFDM frame. The evaluation results show that the proposed system can optimize the frequency window size to enable an efficient timing and frequency offset estimation with high and stable performance in terms of bit error rate (BER) and Frame Error Rate (FER) especially when the value of EbN0 (a normalized signal-to-noise ratio SNR measure) is greater than 8 dB, thanks to the wavelet transform.